Diverse cellular morphologies during lumen maturation in Anopheles gambiae larval salivary glands. Issue 2 (27th December 2020) - Chiu, M.; Trigg, B.; Taracena, M.; Wells, M.
Abstract: Mosquitoes are the greatest animal threat to human health, causing hundreds of millions of infections and around 1 million deaths each year. All mosquito‐borne pathogens must traverse the salivary glands (SGs) to be transmitted to the next host, making this organ an ideal target for interventions. The adult SG develops from precursor cells located in the larval SG duct bud. Characterization of the larval SG has been limited. We sought to better understand larval SG architecture, secretion and gene expression. We developed an optimized method for larval SG staining and surveyed hundreds of larval stage 4 (L4) SGs using fluorescence confocal microscopy. Remarkable variation in SG cell and chromatin organization differed among individuals and across the L4 stage. Lumen formation occurred during L4 stage through secretion likely involving a coincident cellular apical lipid enrichment and extracellular vesicle‐like structures. Meta‐analysis of microarray data showed that larval SG gene expression is divergent from adult SGs, more similar to larval gastric cecae, but different from other larval gut compartments. This work highlights the variable cell architecture of larval Anopheles gambiae SGs and provides candidate targets for genetic strategies aiming to disrupt SGs and transmission of mosquito‐borne pathogens. Abstract : We surveyed hundreds of larval Anopheles gambiae salivary glands (SGs) to better understand their architecture, function and how adult SGs arise. We uncovered remarkable variability in cell size and shape, as well as evidence of extracellular, vesicular secretion, not observed in adult SGs. Through meta‐analysis, we compared gene expression profiles of larval SGs with adult SGs and larval/adult gut and reproductive tissues to define a new class of candidate SG intervention targets.